Sexual Violence and Reproductive Health Outcomes Among South African Female Youths: A Contextual Analysis - Speizer, Ilene S. (American Public Health Association, 2009)
Objectives. We studied whether female youths from communities with higher sexual violence were at greater risk of negative reproductive health outcomes. Methods. We used data from a 2003 nationally representative household survey of youths aged 15–24 years in South Africa. The key independent variable was whether a woman had ever been threatened or forced to have sex. We aggregated this variable to the community level to determine, with control for individual-level experience with violence, whether the community-level prevalence of violence was associated with HIV status and adolescent pregnancy among female, sexually experienced, never-married youths. Results. Youths from communities with greater sexual violence were significantly more likely to have experienced an adolescent pregnancy or to be HIV-positive than were youths from communities experiencing lower sexual violence. Youths from communities with greater community-level violence were also less likely to have used a condom at their last sexual encounter. Individual-level violence was only associated with condom nonuse. Conclusions. Programs to reduce adolescent pregnancies and HIV risk in South Africa and elsewhere in sub-Saharan Africa must address sexual violence as part of effective prevention strategies.